A Note of Education, Pluralism and Ideology - Ronald K. Goodenow (Educational Considerations, 1976)
Programs on ethnicity and pluralism may not only be self-serving, but like a great deal that passes for educational reform or change, designed to preserve institutional homeostasis and integrity.